A quality by design framework for developing nanocrystal bioenabling formulations - Simões, Ana; Castro, Ricardo A.E.; Veiga, Francisco; Vitorino, Carla (International journal of pharmaceutics, 2023)
[Display omitted] The present study aims to outline a rational framework for the design and development of a 1.0% (w/v) hydrocortisone nanocrystal-based formulation, resorting to a simple, efficient, and scalable nanonization methodology, based on the high-pressure homogenization (HPH) technique. Accordingly, the innovative product was comprehensively optimized following a Quality by Design (QbD) approach. The thorough selection of formulation composition was driven by a dual purpose: improving skin permeation and stability. In the early stage of development, a Failure Mode, Effects and Criticality Analysis (FMECA) diagram was employed to identify the most impactful variables for the critical quality attributes (CQAs). In this sense, a rotatable, three-factor and five-level circumscribed central composite design (CCCD) was applied to investigate how squalene concentration (x1), soluplus concentration (x2) and HPH-time (x3) influence physicochemical properties, performance and physical stability of the formulation. A robust Design Space (DS) was defined, establishing the optimal settings for the critical variables, whose combination meets the requirements set in the quality target product profile (QTPP). Morphological analysis revealed the cuboidal shape of hydrocortisone nanocrystals. In what concerns colloidal properties, the most promising formulation disclosed a small particle size (Dx(50) = 311.8 ± 1.5 nm), along with narrow size distribution (span value = 1.91 ± 0.17). Zeta potential results (−2.19 ± 0.15 mV–−12.1 ± 0.4 mV) suggested a steric hindrance stabilization. FTIR spectra showed no chemical interactions between drug and formulation components. XRD diffractograms confirmed loss of crystallinity during the downsizing process. In vitro studies revealed an improvement on drug release rate (316 ± 21–516 ± 35 μg/cm2/√t), compared to the coarse suspension and commercial products, and a straight dependence on the stabilizer concentration and HPH time. The permeation flux across the skin (0.16 ± 0.02–1.2 ± 0.5 μg/cm2/h) appeared to be dependent on the drug physicochemical properties, in particular saturation solubility. Further characterization of the experimental formulations pointed out the role of the stabilizing component to prevent against physical instability phenomena. This organic solvent-free, and therefore “green” nanocrystal production technology offers great potential for pharmaceutical R&D and drug delivery by enabling the development of new forms of conventional drugs with optimal physicochemical properties and performance.